Juridical Review of the Process of Investigating Online Prostitution Crimes in Indonesia Based on National Police Regulation No. 6 of 2019 concerning Criminal Investigation (Peraturan Kapolri No. 6 Tahun 2019) - Rumadi Rumadi; Vivi Sylvia Purborini (Cita Konsultindo Research Center, 2024)
Online prostitution has become a new mode, namely by offering woman via a web address. The owner of this website displays photos of women with minimal clothing ready to serve customers, Criminal Law incl in public law which Law Criminal law materially criminal law or the Criminal Code as regulations legislation that regulates everything material criminal acts and as the formal implementer of criminal law known as the Criminal Procedure Code. The type of research used by the author in this research is Library research is also known as Library Research describe systematically, normatively, and accurately the object becomes the main problem. In conclusion, Settings law about investigation And investigation has been regulated in the Criminal Procedure Code and Perkap No. 6 of 2019 Concerning Criminal Investigation. Implementation investigation And investigations in Indonesia already based on the Criminal Procedure Code and Regulations National Police Chief Number 6 of 2019 Concerning Criminal Investigation and it's been running well in every region.